1978
DOI: 10.1080/03610737808257141
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive maps of environmental knowledge and preference in nursing home patients

Abstract: Two studies examined cognitive maps of environmental knowledge and preference shown by nursing home patients. In study I, knowledge of the nursing home environment was investigated. Age was found to be negatively related to accuracy in identifying the locations of slide-depicted scenes. Also, patients who had lived several years in the nursing home were less able to identify the locations than were students who received a five-minute exposure to each area. Variable identification performance across areas was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…This lack of salience can have profound consequences. For example, there is evidence that nursing home residents with intact cognition often do not recognize common areas within their own residence and show an overwhelming preference for their own rooms (Weber, Brown, & Weldon, 1978), perhaps because they are fearful of getting lost. Likewise, Passini and colleagues (2000) showed that nursing home residents with dementia are often unable to find their way from one place to another within their facility.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of salience can have profound consequences. For example, there is evidence that nursing home residents with intact cognition often do not recognize common areas within their own residence and show an overwhelming preference for their own rooms (Weber, Brown, & Weldon, 1978), perhaps because they are fearful of getting lost. Likewise, Passini and colleagues (2000) showed that nursing home residents with dementia are often unable to find their way from one place to another within their facility.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, very little environmental cognition research has been conducted with the elderly. A few preliminary studies suggest that the elderly have more restricted, less accurate cognitive maps of their immediate neighborhoods (Walsh, Krauss, and Regnier 1981), and have greater difficulty orienting in institutional environments (Weber, Brown, and Weldon 1978). Gerontologists interested in planning for the elderly have noted that impaired memory and perceptual functioning in the elderly plus restricted mobility make them a population with special planning needs (Lawton 1970;Pastalan and Carson 1970).…”
Section: Urban Form and The Elderlymentioning
confidence: 97%
“…In normal aging humans and in individuals with AD, to a more severe degree, there is deterioration in episodic memories [98,99] as well as working and spatial memory [98,99]. Importantly, the hippocampus is also one of the most age-sensitive areas in the brain, and it is thought that the aging process greatly diminishes the plastic capabilities of this region and these declines lead to the age-related impairments in cognitive output.…”
Section: Behavioral Characteristicsmentioning
confidence: 99%